Avaliação do efeito de duas linhagens de Lactococcus lactis na ancilostomose experimental - Thayse Batista Moreira (2016)
Ancylostomiasis is a neglected tropical disease that affects about 740 million people worldwide and is the leading cause of anemia in children and pregnant women. Probiotic organisms, such Lactococcus lactis subsp lactis NCDO2118, act in the gastrointestinal tract by modulating the immune response directly or inducing oral tolerance to antigens. The HSP65 protein is highly present in inflamed environments being inhibited by specific TREG cells. This molecule has been used to induce growth of this cell type and to create an environment less susceptible to inflammation in diseases as ulcerative colitis and Crohn's disease. This study evaluated the effect of using L. lactis subsp lactis NCDO2118 in experimental ancylostomiasis, by two different approaches, using a protocol to assess the effect of oral tolerance to Hsp65 (experiment I) and by direct modulation of L. lactis lactis NCDO2118 (experiment II) both in hamster (Mesocricetus auratus) infected with Ancylostoma ceylanicum. In the first experiment, the animals were divided into six groups: untreated and uninfected (NT + NI), untreated and infected (NT + I), treated with M17 medium and infected (T + I), wild L. lactis lactis NCDO2118 and infected (NCDO + I), L. lactis lactis NCDO2118 (pXylT:SEC:nuc) and infected (NCDO R + I), L. lactis lactis NCDO2118 expressing Hsp65 (pXylT:SEC:hsp65) and infected (HSP65 + I). Treatment was conducted over four days, with the culture administrated to the animals ad libitum. After seven days, animals were orally infected with 50 larvae (via gavage). This infection was monitored for 30 days by measuring, the animals weight; blood cells; total protein in serum and eggs per gram of feces (O.P.G.). On the day of euthanasia adult worms were recovered from the small intestine and mesenteric lymph node kept to later detection of cytokines. In this experiment, no difference was observed among treatments in the evaluated parameters, not allowing to infer that oral tolerance has been established and that it interfered with the course of infection. In the second experiment, the animals were divided into groups: untreated and infected (NT + I) treated with wild L. lactis lactis NCDO2118 initiated with zero days of infection (NCDO - 0), treated with L. lactis lactis NCDO2118 expressing Hsp65 (pXylT:SEC:hsp65) started with zero day infection (HSP65 - 0) treated with wild L. lactis initiated at eight days of infection (NCDO - 8) and treated with L. lactis lactis expressing Hsp65 (pXylT:SEC:hsp65) initiated at eight days of infection (HSP65 - 8). Treatments were administered for four days ad libitum. All groups were infected with 50 larvae on day zero. The infection was monitored for 30 days and the same parameters described above, were evaluated. The groups that were treated on day zero of infection showed a lower parasite load than the other groups, interfering with the other parameters evaluated. The groups treated with eight days of infection showed a higher parasite load compared to the control group with the related parameters also being changed accordingly. This study shows that the protocol used for the induction of Hsp65 oral tolerance was ineffective in ancylostomiasis, however, the use of L. lactis lactis NCDO2118 can interfere with parasite load in the host.